Advantages and Disadvantages of Using 3D Printing by Science Teachers - Syinta Khefrianti; Asep Kadarohman; Wiji; Wandy Praginda (Jurnal Penelitian Pendidikan IPA, 2024)
3D printing transforms abstract contexts into more concrete ones and effectively enhances creativity. The purpose of this study is to explore the benefits and challenges teachers face in using 3D printing. The research method used in this study involved a narrative review of various literatures related to the use of 3D printing by science teachers. The results of this study show that there are benefits in using 3D printing as well as barriers experienced by science teachers. The benefits obtained by teachers are not only limited to themselves but also colleagues due to collaboration and of course for students. Teachers' pedagogical skills in designing lessons and using technology also experienced positive changes. Meanwhile, the obstacles in using 3D printing are also felt by teachers such as limited teacher skills, availability of tools and the use of tools that are relatively time-consuming.